2010
DOI: 10.1136/adc.2009.164848
|View full text |Cite
|
Sign up to set email alerts
|

Maternal postnatal depression and children's growth and behaviour during the early years of life: exploring the interaction between physical and mental health

Abstract: Maternal postnatal depression is associated with later child behaviour problems independent of the socioeconomic status of the family. This association is mediated by the child's growth, demonstrating the importance of considering a child's physical and mental health together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(126 citation statements)
references
References 56 publications
(37 reference statements)
6
113
2
5
Order By: Relevance
“…For example, we know that there are strong socio-cultural influences in some settings (not only in LLMICs) on the gender balance of offspring, and that this can have profound effects on women's propensity to develop PND (Ahmad & Khan, 2005;Xie et al, 2007). Finally, we know that there are many studies from upper middle income countries that might have relevance for understanding the relationships between PND and poverty, but that were excluded on the basis of our geographic limitations, for example, (Avan et al, 2010;Beard et al, 2005;Cooper et al, 2009;Cooper et al, 1999;Danaci et al, 2002;Ramchandani et al, 2009;Tomlinson et al, 2004).…”
Section: Study Limitationsmentioning
confidence: 99%
“…For example, we know that there are strong socio-cultural influences in some settings (not only in LLMICs) on the gender balance of offspring, and that this can have profound effects on women's propensity to develop PND (Ahmad & Khan, 2005;Xie et al, 2007). Finally, we know that there are many studies from upper middle income countries that might have relevance for understanding the relationships between PND and poverty, but that were excluded on the basis of our geographic limitations, for example, (Avan et al, 2010;Beard et al, 2005;Cooper et al, 2009;Cooper et al, 1999;Danaci et al, 2002;Ramchandani et al, 2009;Tomlinson et al, 2004).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Maternal postnatal depression has been linked to short and long-term negative effects for the child's behaviour, emotional and social wellbeing [e.g. 1,12].…”
Section: Introductionmentioning
confidence: 99%
“…There is good evidence that PPD is associated with poorer child cardiovascular functioning [40], gastrointestinal infections and lower respiratory tract infections [41]. Finally, other studies provide evidence that PPD affects child growth [42,43].…”
Section: Secondmentioning
confidence: 99%
“…Recent longitudinal studies showed that maternal depressive symptoms experienced during the first six months postpartum are associated with internalizing and externalizing psychopathology from early childhood to adolescence [35,36].…”
Section: Secondmentioning
confidence: 99%